Faktor Suku Bunga, Kepercayaan, Transparansi, dan Edukasi Keuangan terhadap Praktik Akuntansi Keuangan di Koperasi Wilayah Kabupaten Nganjuk - Denta Fitrina Almayra; Indrian Supheni; Ambarwati Ambarwati (AKUNTANSI 45, 2026)
Savings and loan cooperatives in Nganjuk Regency play an important role in improving the welfare of the community through the provision of inclusive and sustainable financial services, especially for small and medium business actors. However, the financial accounting practices that are implemented still face various challenges, especially those that come from internal organizational factors, such as financial policies, governance, and the quality of human resources. This study aims to examine the influence of interest rates, trust, transparency, and financial education on the financial accounting practices of savings and loan cooperatives. The research method uses a quantitative approach with survey techniques of 300 respondents consisting of administrators, managers, and cooperative members. Data were collected through a structured questionnaire and analyzed using multiple linear regression after first conducting validity, reliability, and classical assumption tests. The results of the study show that interest rates, trust, transparency, and financial education both partially and simultaneously have a significant effect on cooperative financial accounting practices. In addition, transparency and trust have a dominant contribution in encouraging accurate and accountable financial reporting. These findings affirm the importance of strengthening the internal factors of cooperatives through appropriate policies, increasing financial literacy, and implementing good governance principles to increase the accountability, credibility, and sustainability of cooperatives in Nganjuk Regency.